Magnesium technology 2021 - Miller, Victoria, 1977-; Maier, Petra; Jordon, J. Brian 1979-; Neelameggham, Neal R. (Springer, 2021)
The Magnesium Technology Symposium, the event on which this collection is based, is one of the largest yearly gatherings of magnesium specialists in the world. Papers represent all aspects of the field, ranging from primary production to applications to recycling. Moreover, papers explore everything from basic research findings to industrialization. Magnesium Technology 2021 is a definitive reference that covers a broad spectrum of current topics, including novel extraction techniques; primary production; alloys and their production; thermodynamics and kinetics; cast products and processing; wrought products and processing; forming, joining, and machining; corrosion and surface finishing; structural applications; degradation and biomedical applications; and several others.
"The Magnesium Technology Symposium held during TMS 2021 Virtual Annual Meeting & Exhibition, March 15-18, 2021 ..."--Preface
Keywords: Magnesium -- Congresses.; Magnesium -- Metallurgy -- Congresses.; Magnesium alloys -- Congresses.; Materials science -- Congresses.; elektronické knihy; electronic books